Identification of cryptosporidium parvum parasite oocyst using microscopic &PCR assay for detection GP900gene - Rana Salih Sahib Al-Difaie (Al-Qadisiyah Journal of Pure Science, 2018)
The present study designed to diagnose the parasite Cryptosporidium parvum from patients with diarrhea arrivals to Maternity and Childhood Teaching Hospital and General Education Hospital in Al-Qadisiya Governorate , as well as to investigate and to emphasize the presence of virulence factor Glycoprotein 900 in parasite C. parvum using Conventional PCR Technique, and for these purposes one hundred feces samples were collected from children under 10 years old, for the period between 1 \ 5 \ 2013 - 1 \ 11 \ 2013. The results show presence of Cryptosporidium parvum parasite oocyst in 28 positive samples distributed throughout the months of the study, and then, DNA was extracted from the positive samples and then after amplified using special designed for primers C. parvum virulence factor gene that called Glycoprotein 900 and the amplified DNA passed in electrophoresis apparatus for DNA. The results showed that the mentioned factor is present in all positive samples of C. parvum. The highest percentage of infection with the parasite was in the age group (1-3 years) with (39.2%), followed by age group (less than one year) with (21.4%) and the lowest percentage of infection was in the age group (7-10 years) by 7.1%, whereas the percentages of infection with the parasite in the age groups (5-3) , (7-5) were17.8% , 14.2%, respectively. Also the results of the current study, showed that there are no significant differences according to sex .The number of infected males were about 15 with (53.5%) and the number of infected females were about 13 with (46.4%) , besides the results indicate that the highest percentage of infection was in rural areas rose (57.1%) and the lowest percentage of infection was in the urban (42.8 %).